Implications of climate change for sustainable agricultural production systems in ACP countries Getting information and communication strategies right : Executive Summary: Understanding and Confronting Climate Change: What can be done - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2009)
Summary of adaption and mitigation strategies for reducing the effects of climate change especially with regard to better information and communincation management.